Integration of Science in Islamic Education Practice at PTKIN and PTKIS - Supriatna, Papay (Review: Journal of Multidisciplinary in Social Sciences, 2025)
This study examines the practice of science integration in Islamic education at State Islamic Religious Colleges (PTKIN) and Private Islamic Religious Colleges (PTKIS) in Indonesia. The purpose of the study was to compare models of science integration and analyze the structural challenges faced by both institutions. The research method used a qualitative approach with multiple case studies at UIN Syarif Hidayatullah Jakarta (PTKIN) and UNISMA Malang (PTKIS). The results show that PTKIN adopts a transdisciplinary model based on real projects (for example, the integration of environmental science with Islamic values), while PTKIS tends to use an embedded curriculum due to limited resources. The disparity in budget and qualifications of PTKIN and PTKIS lecturers is a major obstacle. However, collaboration through digital platforms (such as Moodle) and blended learning training has the potential to reduce the gap. This study recommends affirmative policies, strengthening lecturer capacity, and technology consortiums to support holistic science integration, in accordance with the global trend of Islamization of Knowledge.